Tuber yield and nutrient balance of potato (Solanum tuberosum L.) Cultivation as influenced by different nutrients management under AEZ-28 (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at Regional Wheat Research Centre of the Bangladesh Agricultural Research Institute, Joydebpur, Gazipur for 2 consecutive years during 2006-07 and 2007-08. The objectives were to find out the optimum nutrient management practice on tuber yield, nutrient balance and economics of potato cultivation. Twelve nutrient management treatments were tested in a randomized complete block design with 3 replications. Treatments were T1=HYG (0-198-44-194-24-6-1.2), T2=MYG (0-140-34-138-18-4.5-0.9), T3=IPNS (10000-168-38-170-18-6-1.2), T4=STB (0-171-40-164-22-5-1), T5=FP (0-97-16-91-0-0-0), T6=CON (0-0-0-0-0-0-0), T7=HYG+CRI, T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI, T11=FP+CRI, T12=CON+CRI kg ha-1 CDNPKSZnB for potato. The highest tuber yield of potato was obtained from STB+CRI (27.64 t ha-1) followed by IPNS+CRI (27.35 t ha-1), STB (27.10 t ha-1), IPNS (26.83 t ha-1), HYG+CRI (26.52 t ha-1) and HYG (26.10 t ha-1) in 2006- 07. Similar trend was found in 2007-08. The highest tuber yield and yield contributing parameters were noticed in CRI plots than without CRI. Except N, remaining nutrient balance like P K S Zn and B were found positive in case of HYG, MYG, IPNS and STB along with or without CRI nutrient managements. The balance was found almost negative in case of FP and CON. The highest BCR was observed in STB+CRI (3.96) followed by STB (3.93), IPNS+CRI (3.76), and IPNS (3.74). The higher gross return (Tk. 283331 ha-1) and also gross margin (Tk. 211761 ha-1) was observed from the same treatment. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22544 Bangladesh J. Agril. Res. 39(4): 641-659, December 2014